Characterization of Silver(I) Complexes with Halo-Substituted Pyridine Derivatives in Solution and in the Solid State - Roca, Sunčica (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
The coordination chemistry of silver(I) complexes has attracted significant attention due to their antimicrobial and antitumor properties. The flexibility of the silver(I) coordination sphere along with the versatile role of the nitrate ion (bridging, monodentate, bidentate ligand) offers the possibility to create structurally diverse compounds. Moreover, halogen (Cl, Br, I) substitution of the pyridine ring further modulates the properties and behavior of such compounds through halogen and hydrogen bonds. Herein we highlight the importance of structure-property relationships in the development of bioactive compounds. The new silver complexes were prepared by the reaction of AgNO3 and the corresponding pyridine derivative, yielding compounds with the general formula [Ag(NO3)(Xnpy)2], X = Cl, Br, I; n = 1–2. The isolated products were characterized by multinuclear NMR spectroscopy (1H, 13C, 15N, 109Ag), mass spectrometry and single crystal X-ray diffraction data. The bioactivity of the compounds was also tested.